Perceptions of Parents and Children on Implementation of Mid-Day Meal Scheme (Case Study of UT of Chandigarh) - Prakasam, Seepana (JOURNAL OF INDIAN EDUCATION, 2017)
This paper attempts to capture the perceptions of the duo stakeholders (parents and children) on the status of implementation of Mid-Day Meal Scheme (MDMS). Findings of the study are based on randomly selected 500 sample respondents (250 households and 250 school-going children) residing in slums and shanties in Chandigarh. Healthy children are better able than sick or malnourished to go to school and learn, keeping this view under consideration, mid-day meal scheme was introduced in India to increase enrolment, attendance, retention and nutritional status of school children. Parents and children expressed mixed response regarding implementation and impact of MDMS. Children revealed that not taking/discontinuing/wasting/taking less quantity of meal is due to food not being tasty/undercooked/overcooked, fear of insects in the food, monotony due to repetition of one or other type of pulses in weekly menu, etc. Food menu should be maintained by consulting the parents and children, without compromising nutritional values. The proportion of children availing MDMS will be more if food is prepared in the school-based kitchens instead of distribution from the centralised kitchens.